Laminectomy Decompression in Radiculopathy Vertebrae L3-L4, L4-L5: A Case Report - Radityo Priambodo; Sevline Estethia Ompusunggu; Rully Hanafi Dahlan (Talenta Publisher, 2023)
Background: Spinal tumors are uncommon lesions and affect only a minority of the population. Spinal metastases comprise approximately 97% of masses encountered with spinal imaging and are the most common site of metastasis from breast cancer. The signs and symptoms for metastatic spinal tumors vary from back pain, motoric and sensoric dysfunction, and in advanced disease, spinal cord compression. Objective: To report a case of metastatic spinal tumor in a patient with a history of breast cancer presenting with lower limb weakness. Methods: A 39-year-old female patient with complaints of lower limb weakness and a history of breast cancer underwent a contrast lumbosacral MRI examination, revealing metastatic spine tumors. The patient was planned for laminectomy decompression, tumor resection, and posterior stabilization procedures. Results: The MRI confirmed the presence of metastatic spinal tumors. The patient underwent planned surgical interventions including laminectomy decompression, tumor resection, and posterior stabilization. Conclusion: Spinal tumors are conditions that can arise within the spinal cord itself or from adjacent structures and affect only a minority of the population. The hallmark symptom for spinal metastases is back pain. Surgical techniques such as open decompression and stabilization are used based on the patient's condition, particularly in cases with neurodeficits and compression seen on radiological examination, and they offer a good prognosis.